2006
DOI: 10.1016/j.chemphyslip.2006.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Folding kinetics of the outer membrane proteins OmpA and FomA into phospholipid bilayers

Abstract: The folding mechanism of outer membrane proteins (OMPs) of Gram-negative bacteria into lipid bilayers has been studied using OmpA of E. coli and FomA of F. nucleatum as examples. Both, OmpA and FomA are soluble in unfolded form in urea and insert and fold into phospholipid bilayers upon strong dilution of the denaturant urea. OmpA is a structural protein and forms a small ion channel, composed of an 8-stranded transmembrane ␤-barrel domain. FomA is a voltage-dependent porin, predicted to form a 14 stranded ␤-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
85
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 101 publications
7
85
0
Order By: Relevance
“…Kleinschmidt 3 and references therein). Folded, solubilized and unfolded forms of hVDAC1 did not show any differences in electrophoretic mobility, neither in SDS-PAGE nor in native gel 25 analysis.…”
Section: Sds Irreversibly Denatures Hvdac1 At Room Temperaturementioning
confidence: 99%
See 3 more Smart Citations
“…Kleinschmidt 3 and references therein). Folded, solubilized and unfolded forms of hVDAC1 did not show any differences in electrophoretic mobility, neither in SDS-PAGE nor in native gel 25 analysis.…”
Section: Sds Irreversibly Denatures Hvdac1 At Room Temperaturementioning
confidence: 99%
“…Folded OMPs of bacteria are usually stable in SDS at RT and migrate differently when not heat-denatured prior to SDS-PAGE (see e.g. Kleinschmidt for a review 3 ). This was not observed for hVDAC1 as a consequence of the altered secondary (and tertiary) structure in SDS.…”
Section: Structure and Stability Of Hvdac1 In Lipid Bilayers And Detementioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, several studies have demonstrated that periplasmic proteins can serve as molecular chaperones in the assembly pathway of OMPs. For example, deletion of the genes encoding the 17-kDa Skp protein or the 48-kDa protein survival factor A (SurA) resulted in reduced concentrations of OMPs in the OM (17). Skp, SurA, and DegP are parts of a functional network that is vital for proper protein folding and degradation in the cell envelope (29).…”
mentioning
confidence: 99%